KOORDINASI CAMAT DALAM PELAKSANAAN PEMBANGUNAN DI KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - SAROINSONG, NITREESILIA ROHSYANI; Posumah, Hanny Johnny; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : As the head of the working area of the districts Head has the authority tocoordinate the implementation of development in the district. The purpose of this study was todetermine how the sub-district coordination in the implementation of development in the districtKauditan North Minahasa Regency.This study used qualitative methods. The informants as many as 10 people, namely: Head,section head of Economic Development, Head of Unit Office (2 people), the Head of Vertical (2people), the village head (2 people), the Chairman of BPD (1 people) and Chairman of the LPM (1people ). Data collection techniques used were interviews. The data analysis was done by usingqualitative analysis interactive model of Miles and Hubernann.The results showed: (1) Coordination Head of the program planning / development activities in thedistrict Kauditan well done and quite effective; (2) Coordination Head towards the implementation ofthe program / development activities in the district Kauditan well done and quite effectiveBased on the results of these studies conclude that camat coordination in theimplementation of development in the district Kauditan implemented properly and fairly effective. Thismeans that the district head coordination in the implementation of development in the district ofcreating or realizing harmony, harmony, balance, synchronization, and integral developmentprograms in the district, and the implementation of development programs can be run on a regular,orderly, smooth and successful.Based on the conclusions of the study and some of the findings in this study, may putforward suggestions: (1) coordination of existing facilities such as meeting coordination, consultationforums, reporting, query data / information needs to be improved the quality of its implementation; (2)Good coordination and effective can be realized optimally only if there is good cooperation andharmony between the coordinating and coordinated.Keywords: coordination, district, development.